STUDI EKSPERIMEN PENGARUH PERUBAHAN KADAR AIR TERHADAP NILAI CBR TANAH LEMPUNG DI LABORATORIUM - Eufronia Herlian Sukacita; Cahyaning Kilang; Indra Suharyanto (JURNAL ILMIAH NUSANTARA, 2025)
This study aims to determine the effect of water content variation on the California Bearing Ratio (CBR) value of clay soil through laboratory testing. Clay soil is a type of soil that is highly influenced by its water content, so any change in moisture level can affect its strength and bearing capacity. The tests were conducted on several soil samples with different moisture contents to determine the optimum water content that yields the maximum CBR value. The results showed that the highest CBR value of 19.23% was obtained at a water content of 39.24% before soaking, which was identified as the optimum moisture content. After a 4-day soaking period, the water content increased to 44.53% and the CBR value decreased, accompanied by a reduction in dry density from 1.02 g/cm³ to 0.93 g/cm³. This condition indicates that excessive water content can reduce soil density and particle cohesion, thereby decreasing the soil’s ability to withstand loads. Therefore, controlling moisture content is essential in construction planning, especially for clay soils that are highly sensitive to moisture changes.